Implementation of organizational changes in Estonian companies - Alas, Ruth (Journal of Business Economics and Management, 2008)
Both the popular press and academic literature tend to consider organizational change as a step‐by‐step process leading to success. This paper examines the suitability of the theory that guides the implementation of change at company level for organizations in countries in transition. The author's surveys, conducted in 137 Estonian companies in 2001 and 121 in 2005, show that the main focus of Estonian managers has been on initiating change and much less attention paid to assessing the process of change and making modifications and consolidating improvements. A process model of change for countries in transition has been proposed.First published online: 14 Oct 2010